Effect of sulphur dioxide and ozone on spore germination of four pathogenic fungi - M. WAJID KHAN, SHAZIA SIDDIQUI and (Indian Phytopathology, 2002)
Sulphur dioxide and ozone inhibited spore germination of Sphaerotheca fuliginea, Helminthosporium oryzae [Cochliobolus miyabeanus], Alternaria alternata and Fusarium moniliforme [Gibberella fujikuroi]. Highest inhibition occurred at 0.2 ppm of bothgases. Increase in exposure duration enhanced the percentage inhibition of spore germination. Inhibition of spore germination was greater with ozone than sulfur dioxide.